Antimicrobial prophylaxis for ureterorenoscopic surgery - Awati, Shreeharsha Mallappa (International Surgery Journal, 2016)
The necessity of antimicrobial prophylaxis (AMP) for ureterorenoscopy is undisputed. Most guidelines state that single AMP is sufficient for ureteroscopy, but indiscriminate antibiotic use is common. Except for transurethral resection of prostate and prostate biopsy, there is a lack of well-performed studies investigating the need and duration of antibiotic prophylaxis in endourology. Although single dose AMP is a widely accepted principle, still multiple-dose regimens are used in some centers. A systematic review was done to know the AMP for ureteroscopy using PubMed articles and Urological Association guidelines. It was concluded that a single dose AMP is necessary for ureterorenoscopic surgery. Either a fluoroquinolone or a combination of ampicillin and aminoglycoside can be used as prophylactic antibiotic.